2018
DOI: 10.5489/cuaj.5021
|View full text |Cite
|
Sign up to set email alerts
|

Dual usage of a stone basket: Stone capture and retropulsion prevention

Abstract: Introduction: Stone migration during ureteroscopy (URS) for proximal ureteric calculi is a constant challenge. Several retropulsion prevention devices have been developed in order to optimize URS outcomes. Our technique involves capturing the stone within a four-wire Nitinol stone basket and then preforming laser lithotripsy to dust the stone while it is engaged in the basket. The dusted fragments wash out with the irrigation fluid and once small enough, the remaining stone is removed intact. Methods: A retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…In his study with a small group of patients, Kesler et al [9] determined the complete stone-free rate to be 100%, but he did not refer to stone localization or stone migration. In another study investigating the dual use of a basket catheter, Kroczak et al [10] reported stone migration in 10 patients (14.7%), which is similar to the rate determined in the current study (five patients; 11.4%). However, the requirement of switching to FURS was lower in our study (two patients; 5.5%) compared to the study by Kroczak et al [10] (19 patients; 24.1%).…”
Section: !"#$%And;(and)*+"-/*0and*1and23%and/294<and"04and6*02-*$and5-*9/and0and2%-+/and*1and23%and*%-"2*0and*926*+%/and "04and6*+$6"2*0/supporting
confidence: 89%
See 3 more Smart Citations
“…In his study with a small group of patients, Kesler et al [9] determined the complete stone-free rate to be 100%, but he did not refer to stone localization or stone migration. In another study investigating the dual use of a basket catheter, Kroczak et al [10] reported stone migration in 10 patients (14.7%), which is similar to the rate determined in the current study (five patients; 11.4%). However, the requirement of switching to FURS was lower in our study (two patients; 5.5%) compared to the study by Kroczak et al [10] (19 patients; 24.1%).…”
Section: !"#$%And;(and)*+"-/*0and*1and23%and/294<and"04and6*02-*$and5-*9/and0and2%-+/and*1and23%and*%-"2*0and*926*+%/and "04and6*+$6"2*0/supporting
confidence: 89%
“…In another study investigating the dual use of a basket catheter, Kroczak et al [10] reported stone migration in 10 patients (14.7%), which is similar to the rate determined in the current study (five patients; 11.4%). However, the requirement of switching to FURS was lower in our study (two patients; 5.5%) compared to the study by Kroczak et al [10] (19 patients; 24.1%). Lastly, our higher rate of JJ stent requirement in the control group may be due to the requirement of FURS in more patients in this group.…”
Section: !"#$%And;(and)*+"-/*0and*1and23%and/294<and"04and6*02-*$and5-*9/and0and2%-+/and*1and23%and*%-"2*0and*926*+%/and "04and6*+$6"2*0/supporting
confidence: 89%
See 2 more Smart Citations
“…Though if three wires were still intact, it has been useful in stone lasering, and he reported this method as a unique technique. In the present study, similar to Kroczak's study, the operation time was shorter, and success was higher and the need for a secondary procedure was reduced, and the only difference with the study of Kroczak is the use of pneumatic lithotripter instead of fiber lasers and with this probe, control might be harder with the heavy piston handle and the use of mechanical thrusts, but it's affordable and accessible in comparison to the laser [21]. In another study, wang, et al in China in 2011 investigated the effect of N-trap on proximal ureter stones treatment.…”
Section: Discussionsupporting
confidence: 72%